European Society for Blood and Marrow Transplantation Analysis of Treosulfan Conditioning Before Hematopoietic Stem Cell Transplantation in Children and Adolescents With Hematological Malignancies. Issue 1 (23rd September 2015) - Boztug, Heidrun; Sykora, Karl‐Walter; Slatter, Mary; Zecca, Marco; Veys, Paul; Lankester, Arjan; Cant, Andrew; Skinner, Roderick; Wachowiak, Jacek; Glogova, Evgenia; Pötschger, Ulrike; Peters, Christina
Abstract : Background: Standard myeloablative conditioning regimens for children with hematological malignancies undergoing allogeneic HSCT are based mainly on total body irradiation or busulfan. Their serious short‐ and long‐term side effects warranted the exploration of less toxic alternatives. Treosulfan is increasingly used for adults and children before HSCT due to its potent immunosuppressive and cytotoxic effects combined with low organ toxicity. Procedure: To further investigate the role of treosulfan conditioning in children, the EBMT Pediatric diseases working party performed a retrospective analysis of 193 children with hematological malignancies (ALL n = 71, AML n = 47, MDS/MPS n = 40, other leukemia/lymphoma n = 25) undergoing allogeneic HSCT following treosulfan between January 2005 and July 2010. Results: Early regimen‐related toxicity was low and mainly gastrointestinal. Veno‐occlusive disease and neurological toxicity were rare. There was no association of toxicity with type of disease or treosulfan dose. High‐grade early toxicity was not higher in infants or patients undergoing second or later transplantation. Treatment related mortality was low at 14%. Three‐year event‐free survival was 45 ± 4% and not significantly influenced by number of transplants, however it appeared to be significantly better for infants ( P  = 0.022). When compared to treosulfan plus fludarabine, the combination of treosulfan, fludarabine and an alkylator (either thiotepa or melphalan) resulted in significantly better overall survival (OS, P  = 0.048) and a trend toward better EFS. Conclusions: Treosulfan based conditioning is a safe and effective approach for children with hematological malignancies, including and importantly for infants and those patients undergoing second or later transplantation. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.